2007
DOI: 10.1007/s10067-007-0731-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow edema syndromes of the hip: MRI features in different hip disorders

Abstract: The objectives of this study were to describe the essential magnetic resonance imaging (MRI) features of bone marrow edema syndromes affecting the hip joint. In addition, to evaluate the role of MRI in the assessment of hip joint involvement in different clinical settings that may share similar clinical findings. Thirty-four patients who complained of hip pain were studied consecutively. Of these, 21 were men (61.8%) and 13 were women (38.2%). After clinical assessment of possible hip disease, plain radiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 30 publications
7
38
0
Order By: Relevance
“…A number of studies have shown that subchondral bone marrow edema developes as a result of inflammation in various sites such as the sacroiliac joints, femoral heads, and the shoulders. [14][15][16] The sign of early involvement in AS is subcortical edema. Subcortical edema may be seen at the femoral head, symphisis pubis, and other sites of enthesis (Figure 1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that subchondral bone marrow edema developes as a result of inflammation in various sites such as the sacroiliac joints, femoral heads, and the shoulders. [14][15][16] The sign of early involvement in AS is subcortical edema. Subcortical edema may be seen at the femoral head, symphisis pubis, and other sites of enthesis (Figure 1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…As bone and cartilage are closely interrelated, interventions affecting pain related to bone turnover may influence OA-relevant pain as well. Pain is a central part of the clinical presentation of OA, 6 and may drive patients to seek consultation for the later diagnosis of OA. Many and diverse structural features of the joint have been implicated in the pain associated with OA, including but not limited to the presence of osteophytes in the patellofemoral compartment, focal or diffuse cartilaginous abnormalities, subchondral cysts, bone marrow edema, subluxation of the meniscus, meniscal tears, and Baker cysts.…”
Section: Calcitonin Pain and Osteoarthritismentioning
confidence: 99%
“…Many and diverse structural features of the joint have been implicated in the pain associated with OA, including but not limited to the presence of osteophytes in the patellofemoral compartment, focal or diffuse cartilaginous abnormalities, subchondral cysts, bone marrow edema, subluxation of the meniscus, meniscal tears, and Baker cysts. 6 However, pain perception is highly individual and very few features correlate to pain robustly. 6 Normal adult articular cartilage is thought to be avascular and aneural.…”
Section: Calcitonin Pain and Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Coronal or sagittal images were obtained as necessary, depending on the topography of the marrow changes on the T1-WI. T1-w images were re-obtained after a 0.1 mmol/kg dose of gadolinium was administered (8).…”
Section: Magnetic Resonance Imaging Protocolmentioning
confidence: 99%